The missing Eusarcus: generic relocation of Pucrolia minuta, with synonymic notes (Opiliones: Laniatores: Gonyleptidae) - Acosta, Luis E. (2023)
The objective of this note is to assess the generic placement of Pucrolia minuta (Sørensen, 1884), a very common species in the Paraná-Paraguay basin (Ringuelet 1959; Acosta 2002), which, despite many similarities with Eusarcus, was overlooked in the aforementioned revision (Hara & Pinto-da-Rocha 2010).